Isolation, Identification and Mass production of five Trichoderma spp. on Solid and Liquid Carrier Media for Commercialization - Hewavitharana, N.; Kannangara, S.D.P.; Senanayake, S.P. (International Journal of Applied Sciences and Biotechnology, 2018)
Trichoderma spp. are fast growing fungi, widely used as bio-control agents for controlling soil borne diseases of plants, as well as growth promoters. The present investigation was carried out to isolate and identified fast growing Trichoderma spp. and mass production using low cost widely available solid and liquid carrier materials. Several fungal spp. were isolated and colony and microscopic characterization were observed in order to identify Trichoderma to generic levels following identification keys. Fast growing Trichoderma spp. were confirmed up to species level following ITS-PCR and sequencing. Identified five Trichoderma spp. were inoculated in solid (coir dust, saw dust and parboiled rice) and liquid (coconut water and rice washed water) carrier materials separately under sterile conditions. Viability and stability of each Trichoderma spp. was tested for 180 days at 40 days intervals by calculating the colony forming units per milliliter (CFU/ml). Twelve Trichoderma isolates were identified up to generic level and five Trichoderma isolates were identified as fast growing species based on their growth rates. Following molecular characterization, identities of these five Trichoderma spp. were confirmed as T. viride, T. asperellum, T. virens, T. longibrachiatum and T. harzianum. Trichoderma spp. incubated in solid carrier materials showed higher (106 CFU/ml) values than the liquid carrier materials (104 CFU/ml) after 180th days and it was significantly different. The highest stabilization potential was recorded for parboiled rice (5 x 106 – 8 x 106 CFU/ml) from day 20th to180th for all five Trichoderma spp. Locally available solid and liquid substrates can be used for the mass multiplication of selected Trichoderma spp. to maintain the viability and virulence for long term commercial availability. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 285-293